KINERJA DINAS PEMUDA DAN OLAHRAGA PROVINSI RIAU DALAM PENINGKATAN SARANA DAN PRASARANA OLAHRAGA ATLETIK - Ledy Ipo Neldy; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The performance of Riau Provincial Youth and Sports Office in Increasing Athletic Sports Facilities and Infrastructure, one of which is to establish an educational container and guidance of talented student athlete which is a form of Act Number 3 of 2005 on National Sport System. The Center for Student Education and Training (PPLP) aims to achieve sporting achievement seeds to participate in a tiered and sustainable nationwide sports competition. The purpose of this research is to find out the performance of youth and sport service of riau province, as well as the obstacles faced in fostering the achievement of athletes of Center for Education and Training of Students (PPLP).The method used in this study was conducted with qualitative descriptive, with data collection techniques including observation, interviews, and documentation related to research objectives. as well as literature techniques and all information collected, analyzed, and studied in order to become a unified whole. The location of this research is Department of Youth and Sports ofRiau Province, that is institution responsible in Enhancement of Sport Facility and Athletic Infrastructure.Result of Research Show, Performance of Department of Youth and Sports of Riau Province inthe promotion of sports facilities and infrastructure is still quite minimal and also Funding has been the main thing has not implemented optimal performance, which impacts such as the absence of health services, exercise transport, and exercise tools as well.Keywords: Organization, Performance, Sport Facilities and Infrastructure.